2020
DOI: 10.1126/sciadv.aba7232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional architecture of the mouse photoreceptor network

Abstract: Mouse photoreceptors are electrically coupled via gap junctions, but the relative importance of rod/rod, cone/cone, or rod/cone coupling is unknown. Furthermore, while connexin36 (Cx36) is expressed by cones, the identity of the rod connexin has been controversial. We report that FACS-sorted rods and cones both express Cx36 but no other connexins. We created rod- and cone-specific Cx36 knockout mice to dissect the photoreceptor network. In the wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(161 citation statements)
references
References 59 publications
11
133
0
Order By: Relevance
“…The transsynaptic interaction likely occurs via the second extracellular loop of the Connexin proteins, which is known to mediate interactions between hemichannels (Bai et al, 2018). Our results are complementary to recent analysis of the mouse rod/cone network, where removing Cx36 from one neuron results in the failure of Connexin localization in the adjacent neuron (Jin et al, 2020). Taken together, our results reveal that ZO1b acts as a postsynaptic molecular scaffold that localizes Cx34.1 to the GJ hemiplaque, which in turn ensures Cx35.5 stabilization at presynaptic hemiplaques (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The transsynaptic interaction likely occurs via the second extracellular loop of the Connexin proteins, which is known to mediate interactions between hemichannels (Bai et al, 2018). Our results are complementary to recent analysis of the mouse rod/cone network, where removing Cx36 from one neuron results in the failure of Connexin localization in the adjacent neuron (Jin et al, 2020). Taken together, our results reveal that ZO1b acts as a postsynaptic molecular scaffold that localizes Cx34.1 to the GJ hemiplaque, which in turn ensures Cx35.5 stabilization at presynaptic hemiplaques (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…To learn whether Cx36 contributes to ipRGC-amacrine coupling, we tested whether its elimination would reduce such coupling. Since many neurons presynaptic to ganglion cells contain Cx36, 54 56 a panretinal knockout would disrupt neural signaling extensively and could cause widespread developmental alterations. Thus, we created Opn4 Cre/+ ; Cx36 flox/ flox ; Z/EG mice to knock out Cx36 only in melanopsin-expressing cells and confirmed that Cx36 expression in both plexiform layers largely remained.…”
Section: Discussionmentioning
confidence: 99%
“…A few rods and cones in Opn4 Cre/+ mice express Cre, 17 so we presumably also eliminated these cells’ Cx36 and hence coupling. 56 But since only a few photoreceptors were uncoupled, any impact on inner retinal development was likely minimal, and indeed ipRGC morphologies were similar in the two mouse lines. At any rate, developmental alteration could not have caused the reduction in M2-amacrine and M4-amacrine coupling because all ipRGC types receive rod/cone input, 57 , 58 and so it is inconceivable that disrupting rod-cone interaction would dramatically affect M2 and M4 but have no impact on M3.…”
Section: Discussionmentioning
confidence: 99%
“…Two rod-bipolar cell dendrites terminate beneath each rod ribbon in mouse retina ( Behrens et al, 2016 ). Together with electrical coupling among rods via cones ( Jin et al, 2020 ), shared responses of two such bipolar cells evoked by large multivesicular release events might contribute to the synchrony among AII amacrine cells.…”
Section: Discussionmentioning
confidence: 99%